If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5r(2m + -6) = 0 Reorder the terms: 5r(-6 + 2m) = 0 (-6 * 5r + 2m * 5r) = 0 Reorder the terms: (10mr + -30r) = 0 (10mr + -30r) = 0 Solving 10mr + -30r = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '30r' to each side of the equation. 10mr + -30r + 30r = 0 + 30r Combine like terms: -30r + 30r = 0 10mr + 0 = 0 + 30r 10mr = 0 + 30r Remove the zero: 10mr = 30r Divide each side by '10r'. m = 3 Simplifying m = 3
| 4x-13=7x-19 | | 7x+5=5-bracket(9x-8) | | 12(5+x)=-7(1+3x) | | -3(-3-2x)=51 | | -7m-1+5m=-m-9 | | 4(2x-4)=-24 | | 8x(y-4)= | | 7(5x+2)=224 | | 2x/3-3=3 | | -2(-5-5x)=110 | | 4(5y-9)-24y+70=4(1-21) | | x/2+2=20 | | 4x-4x-20=0 | | (1+9x)*-2y= | | 6x+8=-46-3x | | 8m-4m-6-3+5m=82-1 | | 6x+1=7x+8 | | x+1=-5x+67 | | 3b+1=10+2b | | 4(x+5)-7(x+5)=-3x-15 | | -(3x-4)-(5x-5)+10=-7(x-1)-(5x+7)+3 | | 1.5d+3.25=1+2.35 | | 4x-2=52-5x | | 4(2x+5)=21 | | 7a+63=10a-30 | | 2y=4+y | | 7a+63=10-30 | | 4x-10=6x-32 | | 49X^2+kx+16=0 | | 2(x+1)=2x-9 | | 2x^2-20x-4=0 | | 7+4s=3s |